2003
DOI: 10.1104/pp.103.019976
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Ascorbate Peroxidase Resides within a Subdomain of Rough Endoplasmic Reticulum in Wild-Type Arabidopsis Cells

Abstract: Previously we reported (R.T. Mullen, C.S. Lisenbee, J.A. Miernyk, R.N. Trelease [1999] Plant Cell 11: 2167–2185) that overexpressed ascorbate peroxidase (APX), a peroxisomal membrane protein, sorted indirectly to Bright Yellow-2 cell peroxisomes via a subdomain of the endoplasmic reticulum (ER; peroxisomal endoplasmic reticulum [pER]). More recently, a pER-like compartment also was identified in pumpkin (Cucurbita pepo) and transformed Arabidopsis cells (K. Nito, K. Yamaguchi, M. Kondo, M. Hayashi, M. Nishimur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 64 publications
4
61
0
Order By: Relevance
“…In these cells, myc-FIS1b consistently colocalized with catalase within a few relatively large cytoplasmic structures ( Figure 1D, arrowheads), distinctly different in size and number from the individual normalappearing peroxisomes visible in the neighboring nontransformed cells ( Figure 1D, arrows) or in mock-transformed cells ( Figure 1H) or from the elongated peroxisomes observed in cells overexpressing myc-PEX11d alone ( Figure 1G). The abnormally large structures in Figure 1D, possessing catalase, myc-FIS1b, and PEX11d likely resulted from peroxisome aggregation, as we previously observed in cells overexpressing peroxisome membrane proteins (Mullen et al, 2001;Lisenbee et al, 2003;Murphy et al, 2003;McCartney et al, 2005). In parallel experiments, coexpressions of myc-FIS1b with untagged PEX11e also resulted in the apparent recruitment of myc-FIS1b to aggregated peroxisomes.…”
Section: Subcellular Localizations Of Fis1a Fis1b and Drp3asupporting
confidence: 49%
See 1 more Smart Citation
“…In these cells, myc-FIS1b consistently colocalized with catalase within a few relatively large cytoplasmic structures ( Figure 1D, arrowheads), distinctly different in size and number from the individual normalappearing peroxisomes visible in the neighboring nontransformed cells ( Figure 1D, arrows) or in mock-transformed cells ( Figure 1H) or from the elongated peroxisomes observed in cells overexpressing myc-PEX11d alone ( Figure 1G). The abnormally large structures in Figure 1D, possessing catalase, myc-FIS1b, and PEX11d likely resulted from peroxisome aggregation, as we previously observed in cells overexpressing peroxisome membrane proteins (Mullen et al, 2001;Lisenbee et al, 2003;Murphy et al, 2003;McCartney et al, 2005). In parallel experiments, coexpressions of myc-FIS1b with untagged PEX11e also resulted in the apparent recruitment of myc-FIS1b to aggregated peroxisomes.…”
Section: Subcellular Localizations Of Fis1a Fis1b and Drp3asupporting
confidence: 49%
“…Immunolabeling of protoplasts was done as described previously (Lisenbee et al, 2003;Flynn et al, 2005) with the following modifications. Briefly, 2 to 4 d after transformation, formaldehyde-fixed protoplasts (see above) were adhered to poly-L-lysine-coated slides for 30 min, incubated in 0.33% (v/v) Triton X-100 in PBS for 15 min, and washed twice in PBS.…”
Section: Biolistic Cell Transformation and (Immuno)fluorescence Micromentioning
confidence: 99%
“…In the yeast Yarrowia lipolytica, the peroxisomal membrane proteins Pex2p and Pex16p were shown to traffic through the ER and to acquire core N-linked glycosylation (7). Findings supporting de novo peroxisome biogenesis in close association with the ER were obtained in cells of Y. lipolytica temperature-sensitive for Pex3p function (8), and studies in the plant Arabidopsis showed that peroxisomal ascorbate peroxidase localized to a subdomain of rough ER that could serve as a compartment for posttranslational sorting to peroxisomes (9). In mouse dendritic cells, the peroxisomal membrane proteins Pex13p and PMP70 were found in subdomains of the ER that extended to a peroxisomal reticulum from which mature peroxisome arose (10).…”
mentioning
confidence: 76%
“…Another important, but poorly characterized, aspect of the ER-peroxisome relationship in plants is the nature of the peroxisomal ER (pER) subdomain, a region of the ER at which preperoxisomes are proposed to be formed (Mullen et al, 1999;Lisenbee et al, 2003). The PMPs APX3 and Arabidopsis PEX10 localize to subdomains of the rough ER (Lisenbee et al, 2003;Flynn et al, 2005;Trelease, 2005, 2007).…”
Section: Membrane Protein Trafficking From the Er To Peroxisomesmentioning
confidence: 99%
“…The PMPs APX3 and Arabidopsis PEX10 localize to subdomains of the rough ER (Lisenbee et al, 2003;Flynn et al, 2005;Trelease, 2005, 2007). However, whether these regions are identical and how the intra-ER sorting and segregation of APX and PEX10 (or any other PMP in the ER) is accomplished has not been elucidated.…”
Section: Membrane Protein Trafficking From the Er To Peroxisomesmentioning
confidence: 99%